2017
DOI: 10.2147/ijn.s141407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibitors of endocytosis and NF-kB signal pathway on folate-conjugated nanoparticle endocytosis by rat Kupffer cells

Abstract: The regular accumulation of nanoparticles in the liver makes them hepatotoxic and decreases the circulation time, thus reducing their therapeutic effect. Resolving this problem will be significant in improving bioavailability and reducing side effects. In this study, we reduced the phagocytosis of epirubicin (EPI)-loaded folic acid-conjugated pullulan acetate (FPA/EPI) nanoparticles by Kupffer cells (KCs) through internalization and nuclear factor kappa B (NF-kB) signal pathway inhibitors, thus allowing develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Genomic DNA sequencing detected mutations in the ANGPT2 gene in stable cell lines (c). Immunoblotting showed the expression levels of ANGPT2 in the stable cell lines and their exosomes, which showed that the levels of exosomal ANGPT2 were decreased correspondingly (d) associates with endocytosis, we used the endocytosis inhibitors nystatin and amiloride to treat HUVECs before coculture [32], and we found that the internalization process of exosomal ANGPT2 was blocked ( Fig. 2c, d), suggesting that HCC cell-secreted exosomal ANGPT2 is delivered into HUVECs via exosome endocytosis.…”
Section: Discussionmentioning
confidence: 89%
“…Genomic DNA sequencing detected mutations in the ANGPT2 gene in stable cell lines (c). Immunoblotting showed the expression levels of ANGPT2 in the stable cell lines and their exosomes, which showed that the levels of exosomal ANGPT2 were decreased correspondingly (d) associates with endocytosis, we used the endocytosis inhibitors nystatin and amiloride to treat HUVECs before coculture [32], and we found that the internalization process of exosomal ANGPT2 was blocked ( Fig. 2c, d), suggesting that HCC cell-secreted exosomal ANGPT2 is delivered into HUVECs via exosome endocytosis.…”
Section: Discussionmentioning
confidence: 89%
“…40 In the study carried out by Tang et al, the cellular uptake and cellular internalization mechanisms of nanoparticles in HeLa (high expression of FA receptor) cells were quantitatively detected by the fluorescence method. 41 In the FA receptor-overexpressing HeLa cells, the internalization of FA-decorated nanoparticles was significantly more efficient than undecorated ones due to FA receptormediated endocytosis and cellular macropinocytosis involved in the cellular internalizations of nanoparticles in HeLa cells. Also, the pH-triggered payload release leads to the increased cumulation of drugs in the cells.…”
Section: Discussionmentioning
confidence: 98%
“…These factors can determine whether and how NPs enter into the cells by CME, as well as affecting the uptake of NPs into cancer cells through multiple receptors on the cell membrane. Moreover, the mechanism of the internalization of NPs into cells depends on several variables, including the cell type, particle size, material composition, shape, and surface properties [ 29 ]. The multiple pathway internalization of QD−UA hybrids (especially QDs–C-2028) can provide an explanation of their higher cellular uptake and cytotoxicity in H460 cells, compared to UAs alone.…”
Section: Discussionmentioning
confidence: 99%